1997
DOI: 10.1073/pnas.94.2.684
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tumorigenesis by a cytosine–DNA, methyltransferase, antisense oligodeoxynucleotide

Abstract: This paper tests the hypothesis that cytosine DNA methyltransferase (DNA MeTase) is a candidate target for anticancer therapy. Several observations have suggested recently that hyperactivation of DNA MeTase plays a critical role in initiation and progression of cancer and that its up-regulation is a component of the Ras oncogenic signaling pathway. We show that a phosphorothioate-modified, antisense oligodeoxynucleotide directed against the DNA MeTase mRNA reduces the level of DNA MeTase mRNA, inhibits DNA MeT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(104 citation statements)
references
References 51 publications
1
102
0
Order By: Relevance
“…DNMT1 knockouts are resistant to colorectal tumorigenesis, and antisense knockdowns of DNMT1 reverse tumorigenesis in vitro and in vivo (Laird et al, 1995;MacLeod and Szyf, 1995;Ramchandani et al, 1997). In ovarian cancer, differential DNMT gene expression has been examined, and it has been suggested that alterations in DNMT expression might contribute to the CpG island methylation phenotype (Ahluwalia et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…DNMT1 knockouts are resistant to colorectal tumorigenesis, and antisense knockdowns of DNMT1 reverse tumorigenesis in vitro and in vivo (Laird et al, 1995;MacLeod and Szyf, 1995;Ramchandani et al, 1997). In ovarian cancer, differential DNMT gene expression has been examined, and it has been suggested that alterations in DNMT expression might contribute to the CpG island methylation phenotype (Ahluwalia et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…57,58 The current approach is to inhibit expression or hyperactivity of DNMT1. [59][60][61] However, demethylating agents lead to unavoidable non-specific genomic demethylation causing genomic instability, DNA damage, oncogene reactivation, and promote opportunities for cancer progression. [62][63][64][65] Because the RFTS domain functions as a key regulator of DNMT1 function, targeting RFTS interactions may revert euchromatin-associated DNMT1 activation while also normalizing pericentromeric DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…1A, there is a 6-base pair mismatch between MG88 and the mouse dnmt1 mRNA. We therefore determined whether MG88 would inhibit DNA synthesis in a mouse adrenal carcinoma cell line, Y1, which was previously shown by us to be responsive to a mouse dnmt1 antisense oligonucleotide (23). The results shown in Fig.…”
Section: Dnmt1 Knockdown Reduces the Fraction Of Cells That Are In S-mentioning
confidence: 99%
“…For Western blot analysis of DNMT1, 50 g of nuclear protein was fractionated on a 5% SDSpolyacrylamide gel, transferred to polyvinylidene difluoride membrane, and reacted with the polyclonal anti-DNMT1 antibody (New England Biolabs) at a dilution of 1:2000 in the presence of 0.05% Tween and 5% milk, and it was then reacted with anti-rabbit IgG (Sigma) at a dilution of 1:5000. The amount of total protein per lane was determined by Amido Black staining (23). The intensity of DNMT1 and total protein signal was measured by scanning densitometry, and the ratio of DNMT1/total nuclear protein was calculated.…”
Section: Methodsmentioning
confidence: 99%